(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2020)
Although altruism may seem incompatible with Behavior Analysis principles, behavior analysts have been studying it in diverse ways. This article systematizes behavior-analytic studies on altruism. A search was performed in PsycINFO, IndexPsi and Scielo databases, and in the Revista Brasileira de Terapia Comportamental e Cognitiva, Revista Brasileira de Análise do Comportamento, and Perspectivas em Análise do Comportamento. The words altruism and altruistic were combined with terms related to Behavior Analysis. 16 articles were selected and analyzed. The results indicated a greater number of basic researches compared to theoretical and applied studies, with an increase in publications from 2001. The discussion on altruism also accompanied other debates, mainly related to molar behavior, self-control, cooperation and Behavioral Game Theory. This increase in publications in the last decades suggests the theme relevance and the possibility of its approach by Behavior Analysis.